MUTATION BREEDING OF A RICE DWARF LINE WITH SLIGHT YIELD LOSS UNDER DROUGHT STRESS - Ahmadikhah, Asadollah; Marufinia, Amir; Sharifzadeh, Esmaeil (Plant Breeding and Seed Science, 2018)
Lack of adequate water leading to drought stress is a common constraint in upland cultivation system of rice. a rice mutant line (MT58) was developed in previous research after mutagenesis of cv. Neda by ethyl methane sulfonate (EMS) and selected for dwarfism (18 cm shorter than Neda). The extent of its molecular changes relative to parental cultivar was assessed by SSR and ISSR markers, and the response of the line along with parental cultivar and another mutant line (MTA) to mild and severe water deficit, was evaluated in a field experiment. a molecular assessment by using 41 SSR markers showed that stunt line MT58 had significant molecular difference with two other lines as confirmed by cluster analysis. ISSR assay also proved the considerable mutational effect of EMS on two mutant lines compared to original wild line. Field experiments revealed that limited irrigation caused mild to severe decrease in all the studied traits including chlorophyll contents. In both mild and sever water stress (S1 and S2) dwarf mutant MT58 had not significant differences in plant yield from parental cultivar Neda. In mild water stress cultivar Neda and mutant line MT58, respectively, showed highest (14%) and lowest (3%) yield loss, while in sever water stress mutant lines MTA and MT58, respectively, showed highest (33%) and lowest (19%) yield loss. In severe stress, cultivar Neda had highest plant height, tiller number and plant yield, and mutant MT58 had highest panicle length, total kernels per panicle, fertile kernels and chlorophyll contents. Reduction in chlorophyll content at drought stress condition was correlated with yield loss (0.64 and 0.697 for chl.a and chl.b, respectively). The results of this research obviously confirm that mutant line MT58 despite of its stunt figure did not show yield difference from its parental cultivar in drought stress.